An exploratory study of children's pretend play when using a switch-controlled assistive robot to manipulate toys (2017)
Introduction Assistive robots could be a means for children with physical disabilities to manipulate toys and for occupational therapists to track children's play development. This study aimed to (a) establish if free play set-ups without and with a robot would elicit a developmental sequence of play in typically developing children, (b) determine if the robot affected children's play and (c) observe the play schemes that children performed. Method An experimental crossover design was conducted. Thirty typically developing children between the ages of 3 and 8 years old performed free play activities with conventional toys or unstructured materials without and with a switch-controlled Lego Mindstorms robot. Children's pretend and functional play was analyzed using a coding scheme developed for the present study. Results There was a trend, increasing with age, for pretend play without the robot with unstructured materials (p =.002), and with the robot, for conventional toys (p = 0.015) and unstructured materials (p = 0.027). Younger children exhibited more pretend play without the robot than with it. Conclusion Assistive robots and appropriate play set-ups can provide a method to measure the play development level of children with disabilities, and support pretend play. Suggestions to support pretend play when children with disabilities use assistive robots are discussed. © 2017 The Author(s).